Knowledge regarding pain management among nursing students of Butwal sub-metropolitan city of Rupandehi district, Nepal - Bhattarai, Sigma; Ghimire, Sulochana; Bhusal, Chet Kant; Rana, Chahana (Journal of Chitwan Medical College, 2021)
Background: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. Pain management is an important aspect of patient care and nurses play a significant role in the acute care setting in pain assessment, treatment and management. The study was designed to find out knowledge regarding pain management among nursing students. Methods: A descriptive cross-sectional study was conducted among 199 nursing students, selected by using non-probability enumerative sampling technique. A validated and pre-tested semi-structured self-administered questionnaire was used and collected data were analyzed by using descriptive and inferential statistics with Statistical Package for Social (SPSS) Software Version 20.0. Results: This study revealed that 77.9% of the respondents had knowledge regarding meaning of pain. About21.1%, 34.7% and 70.9% of the respondents had knowledge regarding group of drug used for mild, moderate and severe pain respectively. And about 66.3%, 30.2%, 17.1%, 14.1% and 4.5% of the respondents had knowledge regarding distraction, relaxation, heat and cold application, imaginary meditation and TENS as non-pharmacological measures used for pain management respectively. The findings of the study revealed that 47.7% had low knowledgeregarding pain management. Conclusions: Nearly half of the students had low knowledge regarding pain management. It is recommended to nursing colleges to give more emphasis on assessment of pain and its management and increase practical exposure.